The Chinese dreamscape, 300 BCE-800 CE - Campany, Robert Ford, 1959- (Harvard-Yenching Institute monograph series, 2020)
"Dreaming is a near-universal human experience. But there is no consensus on why we dream or what dreams should be taken to mean. Robert Ford Campany investigates what people in late classical and early medieval China thought of dreams. He maps a common dreamscape-an array of divergent ideas about what dreams are and what responses they should provoke-that underlies texts of diverse persuasions and genres over several centuries. These writings include manuals of dream interpretation, scriptural instructions, essays, treatises, poems, recovered manuscripts, histories, and anecdotes of successful dream-based predictions. In these many sources, we find culturally distinctive answers to questions people the world over have asked for millennia: What happens when we dream? Do dreams foretell future events? If so, how might their imagistic code be unlocked to yield predictions? Could dreams enable direct communication between the living and the dead, or between humans and nonhuman animals? The Chinese Dreamscape, 300 BCE-800 CE sheds light on how people in a distant age negotiated these mysteries and brings Chinese notions of dreaming into conversation with studies of dreams in other cultures, ancient and contemporary. Taking stock of how Chinese people wrestled with-and celebrated-the strangeness of dreams, Campany asks us to reflect on how we might reconsider our own notions of dreaming"--